Cellular prognostic markers in hepatocellular carcinoma. (June 2015) - Buonaguro, Luigi; Tagliamonte, Maria; Petrizzo, Annacarmen; Damiano, Elvira; Tornesello, Maria Lina; Buonaguro, Franco M
ABSTRACT : Hepatocellular carcinoma (HCC) is one of the five big killers worldwide and is frequently associated with chronic hepatitis B and C virus (HBV and HCV) infections. Tumor microenvironment consists of a complex network of cells and factors that plays a key role in the tumor progression and prognosis. This is true also for HCC. Several studies have shown strikingly strong correlation between HCC clinical prognosis and intratumoral infiltration of cells affecting tumor growth, invasion, angiogenesis and metastasis. None of such cells is yet validated for routine diagnostic and prognostic assessment. The present review aims at providing a state-of-the-art of such studies.